Operational dissection of β‐amyloid cytopathic effects on cultured neurons. Issue 5 (13th February 2013) - Callizot, Noelle; Combes, Maud; Steinschneider, Rémy; Poindron, Philippe
Abstract Alzheimer disease (AD) affects mainly people over the age of 65 years, suffering from different clinical symptoms such as progressive decline in memory, thinking, language, and learning capacity. The toxic role of β‐amyloid peptide (Aβ) has now shifted from insoluble Aβ fibrils to smaller, soluble oligomeric Aβ aggregates. The urgent need for efficient new therapies is high; robust models dissecting the physiopathological aspects of the disease are needed. We present here a model allowing study of four cytopathic effects of Aβ oligomers (AβO): oxidative stress, loss of synapses, disorganization of the neurite network, and cellular death. By generating a solution of AβO and playing on the concentration of and time of exposure to AβO, we have shown that it was possible to reproduce early effects (oxidative stress) and the long‐term development of structural alterations (death of neurons). We have shown that 1) all toxic events were linked to AβO according to a specific timing and pathway and 2) AβO were probably the key intermediates in AD pathogenesis. The present model, using Aβ peptide solution containing AβO, reproduced essential neuropathological features of AD; the effects involved were similar whatever the kind of neurons tested (cortical vs. hippocampal). By using a single system, it was possible to embrace all toxic mechanisms at defined times and concentrations, to study each involved pathway, and to study the effects of new molecules on the different neurotoxic pathways responsible for development of AD. © 2013 Wiley Periodicals, Inc.